MENINGKATKAN KEMAMPUAN BERFIKIR SIMBOLIK ANAK USIA DINI MELALUI METODE PERMAINAN FLASHCARD - Ojah Faojah; Siska Yulianti; Ema Aprianti (IKIP Siliwangi, 2020)
This research is important in the teacher's effort to improve the ability to think symbolically in terms of recognizing the age group of 4-5 years. Early childhood is a period in which all aspects of development experienced by children occur in many aspects of development and all life skills that must be developed. Therefore, early childhood is said to be a golden age and is called a sensitive period for children. and after this development has passed, then any intelligence that is used, it is quite difficult to develop intelligence again in an effort to stimulate the development of children's abilities, it is necessary to use appropriate methods. This research develops aspects of the development of symbolic thinking of children aged 4-5 years at our institution, namely the ability to recognize symbols or numbers. The purpose of the researchers conducted this study was to see how much change in the increase in the ability to think symbolically children aged 4-5 years at our institution by playing a flashcard that is equipped with numbers and images. In the research the researchers conducted was to use a Quasi Experiment with the type of design none equivalent to Group Pretst posttest Design. The results of the study showed the results of the SPSS test version version 20. Then from the implementation of the study it was concluded that the conclusions of this study were quite significant in improving the ability to recognize the numbers of children aged 4-5 years.Penelitian ini penting dalam upaya guru untuk meningkatkan kemampuan berfikir simbolik dalam hal mengenal angka kelompok usia 4-5 tahun. Anak usia dini merupakan masa di mana seluruh aspek perkembangan yang dialami anak terjadi dalam banyak aspek perkembangan dan segenap kecakapan hidup yang harus dikembangkan. Maka dari itu, anak usia dini di katakan usia keemasan dan di sebut masa peka bagi anak. dan setelah perkembangan ini lewat, maka kecerdasan apapun yang di pakai, cukup sulit mengembangkan kecerdasan lagi dalam upaya menstimulasi perkembangan kemampuan anak diperlukan adanya penggunaan cara yang tepat. Penelitian ini mengembangkan aspek perkembangan berfikir simbolik anak usia 4-5 tahun di lembaga kami yaitu kemampuan untuk mengenal simbol atau angka-angka. Adapun tujuan peneliti mengadakan penelitian ini untuk melihat seberapa besar perubahan dalam peningkatan kemampuan berfikir simbolik anak usia 4-5 tahun di lembaga kami dengan melakukan permainan flashcard yang dilengkapi dengan angka dan gambar. Metode penelitian yang peneliti laksanakan adalah menggunakan Quasi Eksperimen dengan jenis desain none equivalen Group Pretst posttest Design. Hasil dari penelitian menunjukkan hasil perhitungan uji SPSS versi 20. Maka dari pelaksanaan penelitian tersebut diperoleh kesimpilan penelitian ini cukup signifikan dalam meningkatkan kemampuan dalam mengenal angka anak usia 4-5 tahun.